Prevention of Internet addiction: A systematic review - Vondráčková, Petra; Gabrhelík, Roman (Journal of behavioral addictions, 2016)
Background and aims Out of a large number of studies on Internet addiction, only a few have been published on the prevention of Internet addiction. The aim of this study is provide a systematic review of scientific articles regarding the prevention of Internet addiction and to identify the relevant topics published in this area of interest. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were adopted. The EBSCO, ProQuest Central, and PubMed databases were searched for texts published in English and Spanish between January 1995 and April 2016. A total of 179 original texts were obtained. After de-duplication and topic-relevance review, 108 texts were systematically classified and subjected to descriptive analysis and subsequent content analysis. Results The results of the content analysis yielded the following thematic areas: (a) target groups, (b) the improvement of specific skills, (c) program characteristics, and (d) environmental interventions. Discussion and conclusion Literature on the prevention of Internet addiction is scarce. There is an urgent need to introduce and implement new interventions for different at-risk populations, conduct well-designed research, and publish data on the effectiveness of these interventions. Developing prevention interventions should primarily target children and adolescents at risk of Internet addiction but also parents, teachers, peers, and others who are part of the formative environment of children and adolescents at risk of Internet addiction. Newly designed interventions focused on Internet addiction should be rigorously evaluated and the results published.
Keywords: návykové chování; Humans; internet; Internet use; Internet; interventions; lidé; online gaming addiction; Internet addiction; Behavior, Addictive; prevention